El humanismo como concreción del ideal constitucional - Wilson Herrera LLanos (Revista de Derecho)
From the beginning of humanity until now, ideology has made psible to hide the most infamous confrontations of hate and fear, all this in defense of the principles of freedom and equality. So, as long as Constitutional Law studious continue more worried about the theoretical perfection of their statements than about the sincere service vocation that imposses its social and human rules, the XXI century will not be enough to build a more faire and equitable society.The author finds here the great challenge of constitutional teaching pedagogy.